Survival of Northern Bobwhite on Hunted and Nonhunted Study Areas in the North Carolina Sandhills - Charles F. Robinette; Phillip D. Doerr (National Quail Symposium Proceedings, 2017)
Radio-tagged northern bobwhite (Colinus virginianus) were monitored in the Sandhills region of North Carolina to investigate the influences of hunting on seasonal survival. We used the Kaplan-Meier product limit method with staggered entry design to calculate survival estimates and distributions for 79 radio-tagged bobwhite representing 33 coveys during November-February 1987-89. Estimated winter survival rates for year 1 (59%) and for pooled years (67%) in the nonhunted study areas were greater than in the hunted areas (31 and 45%, respectively; P < 0.05). Survival trends for the second winter were again greater in the nonhunted study areas (7 4%) but not different than hunted study areas (63%; P > 0.05). Avian predation was the major proximate cause of mortality, accounting for 66% of the known losses. Summer whistle count surveys indicated that nonhunted study areas contained more (P< 0.05) whistling bobwhite per station than hunted areas following winter hunting seasons.
Keywords: Colinus virginianus; hunting; North Carolina; northern bobwhite; Sandhills region; survival; whistle counts